Karya Tari â€œSebuah Catatan Harianâ€: Seni sebagai Media Pembelajaran bagi Anak-anak Tuna Rungu - Jonet Sri Kuncoro (Greget, 2009)
This work try to become a reflection, that we are not alone in this world. In this globalization era where communications expand at full speed, there’s still the human being which "live alone" in their own world. Of course it’s not things which they wish for, however, that circumstance was a disability they suffered. Everyone has their own world. But children’s world of deaf people is a world require to get sympathy, empathy, attention as well as heartfelt intention to assist them. At meanwhile art "telling a story" to us through channel of verbal and nonverbal. Because of its sensitivity and because its way give form to experience, art can jar wire in our soul and reach and also activate the parts of from our own experience which cannot be reached and activated by ordinary information. Art was a representative actualization media, grow self confidence up. Art also the therapy applicable for child suffering concentration trouble, co-ordinate body function, even bounce. Others also as medium of forming of ethic kindness, from values which consisted in art itself, and also in its learning process. For the reason, this work try to a little bit flicking away human side of ourself: is there any of us will share and have the empathy with them, disability children or deaf people which live in their own world? This work try to be a reflection for us about that thingKeyword : dance, therapy, education.